First Brachial Cleft Anomalies in Children: An Innovative Surgical Technique Preventing External Auditory Canal Stenosis - Michal Kotowski; Jaroslaw Szydlowski (MDPI AG, 2023)
First branchial cleft anomalies (FBCAs) are rare congenital malformations that require complete surgical removal. A stenosis of the external auditory canal (EAC) may be the consequence of the disease and its treatment. The aim of this study is to present the details and results of an innovative surgical technique using part of the abnormality for reconstruction purposes. This study covered 28 surgically treated children with FCBA between 2014 and 2021. The analysis included the clinical manifestation form of the abnormality, presence of the EAC deformity, histopathological results, complications, and distant results. On the basis of Work's classification system, 15 pediatric patients with type II FBCA and 13 children with type I FBCA were included in the further study. One child with type II FBCA and two with type I FBCA had a normal EAC. The preoperative appearance of the EAC was classified into three main types, each potentially accompanied by a skin ostium of the sinus/fistula in the EAC. Reconstruction with our technique was performed in 14 children (1 with type I FBCA and 13 with type II FBCA). Wound healing was uncomplicated in all cases. No recurrences were observed. This innovative surgical technique of the subtotal resection of FBCAs with simultaneous reconstruction is safe and prevents postoperative EAC stenosis. Despite the deliberate use of part of the abnormality wall for reconstructive purposes, it remained free of recurrences.